EQUALITY OF HUMAN RIGHTS AND THE RIGHTS TO RECEIVE THE COMPENSATION OF CRIMINAL VICTIMS - Kraurat, Vichan (Journal of MCU Nakhondhat, 2020)
The objectives of the study were to reflect the usage in equality of human rights and the rights to receive the compensation of criminal victims in the duties of government officials. The analysis result found that the human rights are fundamental rights inherent to all human beings, whatever nationality, skin color, sex, age, language, religion, status of body or health, religious beliefs, and other opinions, but there was discrimination in compensation for damage to the injured and crime victims. According to the Act Compensation for the injured and compensation and expenses to criminal defendants 2001 and the second amendment in 2016, this was to create the measures to protect the rights and freedoms of individuals, and help the injured and crime victims appropriately and equally. Therefore, government officials in Ministry of Justice aim to reduce inequality in society and comply with equality. The government pays for the compensation to the injured who are the right person, but there are some people who cannot reach this condition. So, it’s a topic about the differences in the equality according to human principles, for instance, some people who are broken up, lack of educational opportunities, lack of legal knowledge and legal rights, may be a victim of exploitation, deception, or rights violation of others who are in superiority. Thus, leading to equality entirely must have a principle that supports the disadvantaged to get a chance and receive the assistance.